From Mrs. G. to Marmee: The Facts of Life and Little Women. Issue 4 (2nd October 2021) - Abate, Michelle Ann
Abstract: This essay gives much-needed critical attention to the 1980s sitcom, The Facts of Life . While the show was a spinoff to the series Diff'rent Strokes, I make a case that its true creative and cultural debt is to a far different source: Louisa May Alcott's 1868 novel, Little Women .